Reliability Analysis of an Elevator System Under Resume Repair Policy - Kharola, Shristi; Ram, Mangey; Singh, Shivani (Journal of Graphic Era University, 2026)
In day-to-day life, elevators and lift systems have become essential for one’s daily operations. It is therefore important to guarantee its reliability and efficiently prioritise repairs of any kind. In this study, for an elevator system, two types of failures are considered. The first is the critical failure of the elevator brought on either by a power issue or mechanical wear. The second is the non-critical failure caused by minor electrical failures like lighting system failure. Since electrical or lighting failures can be temporarily controlled, the critical failure is given priority in system repairs. This study shows how the preemptive resume repair model can be applied to the general maintenance of an elevator system. The primary objective of this study is to assess the reliability parameters under the resume repair policy.